The Influence of Situational Leadership Style, Motivation and Work Environment on Soldiers’ Performance (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The 2nd Supply and Transport Batallion has the main task of providing supplies, maintenance and services by land, water or air. In carrying out its duties, the Battalion is still experiencing several issues. Some of these issuses caused soldiers’ performance to decline. The research aims to analyze the influence of situational leadership style, motivation, and work environment on soldier performance. This study will use a quantitative verification analysis, that is testing the hypothesis through processing field data. Besides that, exploratory descriptive analysis was also carried out. Researchers sorted out 30% of the sample from 380 soldiers, so that there were 114 samples. The sampling technique is Stratified Random Sampling. Data collection techniques used questionnaires and documentation, while data analysis techniques used descriptive statistical analysis and multiple linear regression analysis. The results of the analysis show that situational leadership style, motivation, and work environment have a positive and significant effect on soldier performance. Situational leadership style has a dominant effect on soldier performance.